The Effect of Arytenoidectomy on Functional and Oncologic Results of Supracricoid Partial Laryngectomy. (October 2015) - Basaran, Bora; Unsaler, Selin; Ulusan, Murat; Aslan, Ismet
Objective: The effect of arytenoid resection was investigated in patients who had undergone supracricoid partial laryngectomy (SCPL) by comparing functional and oncologic results between patients with both arytenoids preserved with those with one arytenoid resected. Methods: Patients were divided into 2 groups: (1) both arytenoids preserved SCPL (BASCL) cases and (2) one arytenoid preserved SCPL (OASCL). The functional outcomes of the 2 groups were compared in terms of nasogastric tube removal time, decannulation time, incidence of aspiration pneumonia, and Performance Status Scale Scores for Head and Neck Cancer Patients for the late postoperative period. Additionally, the oncologic outcomes of both groups were compared using the 5-year local control rate, overall survival, disease-specific survival, and larynx preservation rate. Results: Of the 68 patients who were enrolled in the study, 20 of them were in the OASCL group and 48 in BASCL group. There was no statistically significant difference in the early and late functional outcomes, and the oncologic outcomes were also similar. Conclusion: In addition to the proven oncologic safety, arytenoid resection does not increase the functional morbidity of the SCPL.